“When You Thought That There Is No One and Nothing”: The Value of Psychodrama in Working With Abused Women - Bucuţă, Mihaela D.; Dima, Gabriela; Testoni, Ines (Frontiers in Psychology, 2018)
This paper discusses how psychodrama methods and techniques can empower abused women and stimulate changes in their victim role. Through an in-depth exploration, we sought to gain an insider’s perspective of the experiences of change and perceived outcomes for abused women, which could contribute to optimizing gender violence intervention. Theoretically, the study is grounded in the female co-responsibility and trans-generational transmission of women’s victim role from mother to daughter. A mixed methods experimental design employing an explanatory sequential approach to data collection was implemented. A total sample of 33 abused women (15 in the experimental group, and 18 in the control group) was involved in studying the impact of a psychodrama intervention combined with an ecological intervention. Spontaneity and wellbeing, considered in this study as dimensions of empowerment, were measured. Phenomenological interviews were conducted with 7 women three months after the psychodrama intervention ended, and with 6 women five years later. Data was analyzed using the Interpretative Phenomenological Analysis method. The matrix of themes that emerged reflects four overarching themes: the victim, the group experience, the process of change, and the corollary of change. Benefits perceived by the women include trust, hope, increased self-esteem, empowering, and courage to make decisions and changes. Findings describe three paths of change for women who participated in an empowering-oriented psychodrama intervention program: the Proactive - Resilient type, the Active - Resistant type, and the Repetitive - Non-Resilient type. Role-reconstruction and the interruption of trans-generational victim pattern were clear for the proactive type and possible for the active type, while the repetitive type showed minor changes but remained stuck in the victim pattern. As no claims to generalizability can be made, further research is needed to verify the proposed typology on larger samples. Psychodrama, as an action method, can empower abused women and has the potential to stimulate action in women’s lives and initiate adaptive coping strategies leading to resilience. The study ends with several suggestions for assisted resilience specialists.